Simple Synthesis of Substituted 3-Hydroxyfuran-2(5H)-ones - Lisovenko, Natalya Yu.; Nasibullina, Ekaterina R.; Kharitonova, Svetlana S.; Myshkina, Olga A. (Synthesis, 2021)
A convenient and facile approach to functionalized 4-substituted 3,5-dihydroxy-5-(trichloromethyl)furan-2(5H)-ones was developed. This method is based on regioselective synthesis of novel furan-2,3-diones containing the trichloromethyl group and subsequent hydrolysis. The structures of compounds were unambiguously confirmed by single-crystal X-ray diffraction.
Keywords: β-diketones; trichloromethyl derivatives; cyclization; furan-2,3-diones